Iron Deficiency and Overload From Basic Biology to Clinical Medicine - Yehuda, Shlomo.; Mostofsky, David I. (Nutrition and Health, 2010)
Iron deficiency is ever-present among all populations throughout the world irrespective of race, culture, or ethnic background. Even with the latest advances in medicine, improved nutrition, and the ready availability of cheap oral iron, there is still no satisfactory explanation for the widespread occurrence of iron deficiency or for the absence of an effective treatment. Iron Deficiency and Overload: From Biology to Clinical Medicine is an important new text that provides a timely review of the latest science concerning iron metabolism as well as practical, data-driven options to manage at-risk populations with the best accepted therapeutic nutritional interventions. This volume contains the latest data on the importance of iron in the development of the brain and optimal cognitive function. Chapter topics reflect the excitement in current theoretical development and laboratory activity in this area. The distinguished authors address their presentations to professionals and graduate students who need to be better informed about the concepts, methodologies, and current status of the field. Iron Deficiency and Overload: From Biology to Clinical Medicine is an essential text that presents a sampling of the major issues in iron research, from the most basic research level to human applications.